Analisis Pelanggaran Hak Ekonomi Lagu Akad Karya Payung Teduh dalam Penggunaan Kepentingan Komersial - Gina Sonia Kafiar; Ni Komang Irma Adi Sukmaningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
Copyright is a key pillar of the Intellectual Property Rights system, providing legal protection for creative works in the arts sector, particularly musical works. Within the copyright framework, the most crucial aspect is economic rights, namely the exclusive right of creators to derive financial benefit from any use of their works. However, the reality on the ground demonstrates the rampant use of songs for commercial purposes without proper authorization, which directly harms creators. This article analyzes economic rights violations in the context of commercial use, using the case study of the song